YOGA PHILOSOPHY AND AESTHETIC EXPERIENCE IN INDIAN PERFORMING ARTS - Patil, Sujata V; Bhise, Suhas; M. Madhumitha; Bibhu, Vimal; Karwande, Vijay Suresh; Kumar, Alok (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Indian performing arts have been influenced over a long time by yoga philosophy, which highlights harmony of body, mind and consciousness. The study examines how yogic practices are correlated with aesthetic experience in the traditional Indian performance traditions. The paper discusses the role of the principles based on the philosophy of classical yoga in artistic discipline, expressive eloquence, and interaction with the audience. Analysis of yoga philosophy and Indian aesthetic theory is offered conceptually and a case study with yoga-integrated training amongst classical dance performers is presented. Such performance measures as posture stability, breath control, rhythm synchronization, emotional expression, and endurance during the performance were measured prior to and after a structured training program that involves yoga practices. The results show the stable improvement of all measured parameters, though the emotional expression and performance endurance show the highest improvement. The findings of the evaluation of the audience also show that there is higher engagement and a greater aesthetic perception after the training in yoga basis. Such effects indicate that the yogic practices enhance the self-awareness of performers, their concentration, and the expression of messages, which enhances the aesthetic quality of art performances. The study brings out the trans-disciplinary nature of yoga philosophy in the development of physical, cognitive and emotional aspects of performing arts practice. Introducing yoga into modern performing arts education programs will not only improve health and performance of the performers but also increase the authenticity of the art form and retain the philosophical roots of the Indian artistic circles.